2018
DOI: 10.7554/elife.32143
|View full text |Cite|
|
Sign up to set email alerts
|

Non-invasive detection of urothelial cancer through the analysis of driver gene mutations and aneuploidy

Abstract: Current non-invasive approaches for detection of urothelial cancers are suboptimal. We developed a test to detect urothelial neoplasms using DNA recovered from cells shed into urine. UroSEEK incorporates massive parallel sequencing assays for mutations in 11 genes and copy number changes on 39 chromosome arms. In 570 patients at risk for bladder cancer (BC), UroSEEK was positive in 83% of those who developed BC. Combined with cytology, UroSEEK detected 95% of patients who developed BC. Of 56 patients with uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
165
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 138 publications
(177 citation statements)
references
References 93 publications
9
165
0
3
Order By: Relevance
“…Springer et al reported that mutant DNA in urinary pellets from UTUC patients in Taiwan could be detected by NGS at rates of 25.0% ( TERT C228T), 7.1% ( TERT C250T), 10.7% ( FGFR3 S249C), and 5.4% ( PIK3CA E545K). In the current study, we could detect mutations at rates of 39.3% ( TERT C228T), 7.1% ( TERT C250T), 16.1% ( FGFR3 S249C), and 8.9% ( PIK3CA E545K) in urinary cfDNA in Japanese patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Springer et al reported that mutant DNA in urinary pellets from UTUC patients in Taiwan could be detected by NGS at rates of 25.0% ( TERT C228T), 7.1% ( TERT C250T), 10.7% ( FGFR3 S249C), and 5.4% ( PIK3CA E545K). In the current study, we could detect mutations at rates of 39.3% ( TERT C228T), 7.1% ( TERT C250T), 16.1% ( FGFR3 S249C), and 8.9% ( PIK3CA E545K) in urinary cfDNA in Japanese patients.…”
Section: Discussionmentioning
confidence: 99%
“…The mutant TERT promoter allele alters the binding site, recruits transcription factor GABPA, and engages in long‐range chromatin interactions, subsequently stimulating increased TERT promoter activity and enabling tumors to overcome the end‐replication problem and avoid senescence . Springer et al reported the clinical potential of mutant DNA derived from urinary cells (pellets) by targeted sequencing in patients with UBC or UTUC for cancer detection and surveillance. In UBC patients, urinary cfDNA has a higher tumor genomic burden and greater detection potential as a genomic biomarker than urinary pellets .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, bladder cancer is innately exposed to urine, which is also a resource for liquid biopsy. UroSEEK is one of such tests and is a urine‐based molecular assay designed to detect mutations in 11 genes and copy number changes on 39 chromosome arms for the detection and surveillance of bladder cancer . The 11 genes included drug‐targetable genes, such as FGFR3 , ERBB2 and PIK3CA .…”
Section: New Technologiesmentioning
confidence: 99%
“…Although they are thought to share common pathways of carcinogenesis, UTUCs are more invasive at the time of diagnosis, which indicates a more aggressive genetic phenotype. The use of next‐generation sequencing in the detection of mutation in UTUC definitely accelerates and facilitates the understanding of the genomic level in UTUC …”
Section: Etiologymentioning
confidence: 99%